Peningkatan Keterampilan Menulis Teks Prosedur Melalui Metode Peer Tutoring pada Siswa Kelas IX SMPN 27 Makassar - Novalia, Ananda Reski; Hamsa, Akmal; Sarkiah, Sarkiah (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to improve the writing skills of procedure text through peer tutoring method in class IX students of SMPN 27 Makassar. The research method used was Classroom Action Research conducted in two cycles. The research subjects were 36 students, consisting of 16 male students and 20 female students. The instruments used included interviews, observation sheets and writing skill test sheets. Data analysis used quantitative and qualitative approaches. The results showed that despite the improvement in cycle I, some students were still in the good category with an average score of 63% to 71%. After reflection and improvement in cycle II, students' scores increased to 90% to 93% in the excellent category. The results indicated a significant improvement from cycle I to cycle II. The improvement of learning strategies in cycle II contributed to the increase in the number of students who reached the excellent category. It can be concluded that the peer tutoring method is effective in improving the writing skills of procedure texts in grade IX students of SMPN 27 Makassar.